Use of food consumption data of food balance sheets and national food consumption surveys in deterministic long-term dietary exposure assessments of pesticides. (May 2021) - van der Velde-Koerts, Trijntje; Rietveld, Anton; Boon, Polly E.
Abstract: Deterministic long-term dietary exposure estimates of pesticide residues across different countries are called International Estimated Daily Intakes (IEDIs). Effect of using Food Balance Sheets (FBS) or National Food Consumption Surveys (NFCS) to calculate the IEDI was investigated. Presence of aggregated foods tended to increase the IEDI, and clustering of data from countries with comparable dietary patterns tended to decrease the IEDI. Furthermore, IEDIs for global use were not always at least as conservative as those for regional or national use. Risk assessors using these data should be aware of these limitations. As FBS data are only available for the general population and IEDIs are highest for children, a method was developed to convert FBS based IEDIs to indicative IEDIs for children. This may be appropriate if no NFCS data are available for this age group and the critical health-based guidance value is relevant for this age group. Graphical abstract: Image 1 Highlights: Use of global Food Balance Sheets (import, export, use) in dietary exposure assessments of pesticides is not always more conservative than use of National Food Consumption Surveys. Dietary exposure to pesticides tends to increase by aggregation of food consumption data. Dietary exposure to pesticides tends to decrease by country based clustering of food consumption data. Dietary exposure for children can be estimated with caution from Food Balance Sheet data using assumptions for relative body weight and relative food intake compared to adults.